Contribution of Entrepreneurship and Creativity Education to Entrepreneurial Intent in Vocational School Students in the Engineering and Property Engineering Skills - Hidayatulloh, Muhammad Kris Yuan; Aftoni, Aftoni (International Journal for Educational and Vocational Studies, 2020)
This study aims to find out the contribution level of entrepreneurship education and creativity taking into account factors that support entrepreneurs' intents. This type of investigation is ex post facto with a quota sampling technique of 76 students. The results of the investigation are then discussed through literature review of relevant references and research findings so that several factors are found to support / mediate business importance. Studies have found that there is a positive correlation between entrepreneurial education and students' intent in entrepreneurship. The contribution of change in entrepreneurship education partly to intent in entrepreneurship was 32.60%. There is a positive contribution to creativity in students' intents in entrepreneurship. The contribution to allow for creative change in entrepreneurial intent is partially 18.40%. There is a positive contribution between entrepreneurship education and creativity in students' intent in entrepreneurship. Other supporting factors are self-efficacy and locus of control.